Controlled Synthesis of Large‐Scale, Uniform, Vertically Standing Graphene for High‐Performance Field Emitters. (8th November 2012) - Jiang, Lili; Yang, Tianzhong; Liu, Fei; Dong, Jing; Yao, Zhaohui; Shen, Chengmin; Deng, Shaozhi; Xu, Ningsheng; Liu, Yunqi; Gao, Hong‐Jun
<x xml:space="preserve">Abstract</x> Large‐scale, uniform, vertically standing graphene with atomically thin edges are controllably synthesized on copper foil using a microwave‐plasma chemical vapor deposition system. A growth mechanism for this system is proposed. This film shows excellent field‐emission properties, with low turn‐on field of 1.3 V μm−1, low threshold field of 3.0 V μm−1 and a large field‐enhancement factor more than 10 000. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>